2022
DOI: 10.1038/s41598-022-05570-8
|View full text |Cite
|
Sign up to set email alerts
|

Non-invasively accuracy enhanced blood glucose sensor using shallow dense neural networks with NIR monitoring and medical features

Abstract: Non-invasive and accurate method for continuous blood glucose monitoring, the self-testing of blood glucose is in quest for better diagnosis, control and the management of diabetes mellitus (DM). Therefore, this study reports a multiple photonic band near-infrared (mbNIR) sensor augmented with personalized medical features (PMF) in Shallow Dense Neural Networks (SDNN) for the precise, inexpensive and pain free blood glucose determination. Datasets collected from 401 blood samples were randomized and trained wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 23 publications
(22 reference statements)
0
16
0
Order By: Relevance
“…Many noninvasive technologies are currently in development in a variety of industries. 8,9 Reverse iontophoresis, 10 absorbance spectrosco-py, 11 and near-infrared spectroscopy 12 are a few examples. However, none of them have yet attained the sensitivity and precision required to completely replace finger-prick monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…Many noninvasive technologies are currently in development in a variety of industries. 8,9 Reverse iontophoresis, 10 absorbance spectrosco-py, 11 and near-infrared spectroscopy 12 are a few examples. However, none of them have yet attained the sensitivity and precision required to completely replace finger-prick monitoring.…”
Section: Introductionmentioning
confidence: 99%
“…The SSII field encompasses a vast research area with myriad potential clinical applications, and according to our annual reviews of the field, thousands of articles are published each year [2][3][4]. A growing number of research and review papers have been identified from year to year, with a large majority applying machine or deep paper from the sensor informatics subfield reports on a very innovative multiple photonic band nearinfrared (mbNIR) sensor augmented with personalized medical features (PMF) in Shallow Dense Neural Networks (SDNN) for accurate, low-cost, and painless determination of the blood glucose level [7].…”
Section: Introductionmentioning
confidence: 99%
“…[40,41] This system is capable of penetrating the human body surface without causing ionizing radiation damage, offering the potential to achieve continuous detection of glucose concentration in vitro and improve the management of diabetes. [42][43][44][45] However, for biological solutions, the large amount of moisture in the solution leads to the strong absorption of terahertz waves, making direct detection of biological solutions via transmission THz-TDS systems ineffective. [46,47] To address this, there is an urgent need to develop a terahertz sensor that is extremely sensitive to minute changes in hydration state, aiming to balance the absorption of terahertz waves by water and shorten the swelling equilibrium response time, thereby improving detection efficiency of glucose biomolecules.…”
Section: Introductionmentioning
confidence: 99%